Selective Complementarity of Indigenous Leadership: Ninik Mamak’s Role in Livestock Development in Minangkabau, Indonesia - Putra, Riza Andesca; Hariadi, Sunarru Samsi; Muzayyanah, Mujtahidah Anggriani Ummul (Indian Journal of Extension Education, 2026)
Indigenous leadership plays an important role in rural development, but Ninik Mamak's specific contribution as an indigenous leader of the Minangkabau people to livestock development has not been empirically documented. Present research analyzes the influence of Ninik Mamak's role on livestock development from technical, social, and economic aspects. A quantitative method was used in this study to collect data from 210 respondents from 42 livestock groups in West Sumatra Province. A validated and reliable Likert-scale questionnaire was employed for data collection, and multiple linear regression was used for data analysis. The results show that all regression models are statistically significant. Ninik Mamak's decision-making role shows a strong positive effect on all aspects. However, the role of information dissemination does not show a significant impact, whereas the role of cooperation facilitation has significant negative effects on the technical and economic aspects. This study confirms that Ninik Mamak has a significant role in the development of farms with complex patterns. These findings introduce the concept of "selective complementarity" in institutional theory and recommend selective engagement strategies to optimize the role of indigenous leadership.